Is There a Reason to Perform Icsi in the Absence of Male Factor? Lessons from the Latin American Registry of Art - Schwarze-Meza, J (OXFORD UNIV PRESS, 2017)
STUDY QUESTION: Does the use of ICSI offer any outcome advantage over IVF in patients with non-male factor infertility? SUMMARY ANSWER: We did not find any outcome improvement that justifies the routine use of ICSI over IVF in non-male factor ART cycles. WHAT IS ALREADY KNOWN: Since its introduction in Latin America, the use of ICSI has increased substantially, even among patients without male factor infertility. However, it is not clear whether ICSI provides an advantage over IVF in non-male factor infertility. STUDY DESIGN SIZE, DURATION: A retrospective cohort study of fresh cycles performed in 155 ART clinics located in 15 Latin American countries between 2012 and 2014. Records were assessed for 49,813 ART cycles (39,564 ICSI and 10,249 IVF) performed in infertile couples who did not have male factor infertility. Student s t-test was used to analyze normally distributed data, Wilcoxon test to analyze non-normally distributed data, and Fisher s exact test for categorical data. Logistic regression was used to quantify the effect of ICSI on delivery rate, adjusting for age of female partner, number of oocytes inseminated, number of embryos transferred, and transfer at blastocyst stage as possible confounding factors. Poisson regression analysis was used to quantify the effect of ICSI on fertilization rate, adjusting for age of female partner. PARTICIPANTS/MATERIALS, SETTING, METHOD: Cycles with the diagnosis of male factor and use of cryopreserved semen and with a freeze-all strategy were excluded. MAIN RESULTS AND THE ROLE OF CHANCE: After correcting for age of female partner, number of oocytes inseminated, number of embryos transferred and transfer at blastocyst stage, we found that the use of ICSI was associated with a significant decrease in the odds of delivery compared to IVF (odds ratio 0.88, 95% CI 0.84 to 0.93; P < 0.0001). LIMITATIONS REASONS FOR CAUTION: An important limitation of this study is the lack of randomization owing to its retrospective nature. This could result in selection bias, i.e. couples with the worst prognosis undergoing ICSI, or patients with a history of fertilization failure in IVF cycles undergoing ICSI. More than one cycle from the same couple may be included in the study. WIDER IMPLICATIONS OF THE FINDINGS: The lack of an outcome benefit-and, indeed, a reduced likelihood of delivery-following ICSI in non-male factor infertile couples suggests that ICSI may not be the most appropriate clinical approach in these patients.